Isophorone reactor: modelling and performance enhancement - Darda, Pranay J.; Ranade, Vivek V. (Chemical Engineering Journal, 2012)
The production of isophorone in a reactive distillation column was modelled. Mass transfer and heat transfer accompanied by chemical reactions were incorporated in a dynamic non-equilibrium multistage model. A base case simulation was identified and established. The base case simulation showed the value of key performance indicator that is mass ratio of acetone consumed to isophorone produced as 1.54. The computational model was then used to understand and to evaluate influence of various key design and operating parameters on this key performance indicator. Influence of reactor volume, mass transfer coefficient and feed composition, location and temperature was evaluated. The simulated results indicate that the key performance indicator can be improved (reduce acetone consumed per isophorone produced) by manipulating acetone content in the feed and location of the feed. The presented results will be useful for realising performance enhancement of isophorone and other similar reactors. (C) 2012 Elsevier B.V. All rights reserved.
22nd International Symposium on Chemical Reaction Engineering (ISCRE), Maastricht, NETHERLANDS, SEP 02-05, 2012
Keywords: Isophorone; Model; Performance enhancement; Reactive distillation